Bifurcation of Traveling Wave Solutions for a Two-Component Generalized θ-Equation. (13th December 2012) - Wen, Zhenshu
Abstract : We study the bifurcation of traveling wave solutions for a two-component generalized θ -equation. We show all the explicit bifurcation parametric conditions and all possible phase portraits of the system. Especially, the explicit conditions, under which there exist kink (or antikink) solutions, are given. Additionally, not only solitons and kink (antikink) solutions, but also peakons and periodic cusp waves with explicit expressions, are obtained.